The abundance of the long intergenic non-coding RNA 01087 differentiates between luminal and triple-negative breast cancers and predicts patient outcome. (November 2020) - De Palma, Fatima Domenica Elisa; Del Monaco, Valentina; Pol, Jonathan G.; Kremer, Margerie; D'Argenio, Valeria; Stoll, Gautier; Montanaro, Donatella; Uszczyńska-Ratajczak, Barbara; Klein, Cecilia C.; Vlasova, Anna; Botti, Gerardo; D'Aiuto, Massimiliano; et al.
Graphical abstract: Highlights: LINC01087 is significantly downregulated in TNBCs and upregulated in the luminal BC subtypes. Variation of the level of LINC01087 in the different BC subtypes coincided with modulated expression of factors (mostly secreted) regulating genome integrity and expression, cell survival, cell proliferation, adhesion, invasion, inflammation and drug sensitivity. Deregulation of LINC01087 allowed to accurately distinguish luminal and TNBC specimens, independently of the clinic-pathological parameters, and of the histological and TP53 or BRCA1/2 mutational status. The expression of LINC01087 seemed to exhibit tumor suppressive properties, allowing to predict a better survival in BC subtypes. LINC01087 is a highly specific biomarker for diagnosing and prognosing luminal and TNBC BC subtypes and for predicting the response to pharmacological interventions. Abstract: The molecular complexity of human breast cancer (BC) renders the clinical management of the disease challenging. Long non-coding RNAs (lncRNAs) are promising biomarkers for BC patient stratification, early detection, and disease monitoring. Here, we identified the involvement of the long intergenic non-coding RNA 01087 (LINC01087) in breast oncogenesis. LINC01087 appeared significantly downregulated in triple-negative BCs (TNBCs) and upregulated in the luminal BC subtypes in comparison to mammary samples from cancer-free women and matched normal cancer pairs. Interestingly, deregulation of LINC01087 allowed to accurately distinguish between luminal and TNBC specimens, independently of the clinicopathological parameters, and of the histological and TP53 or BRCA1/2 mutational status. Moreover, increased expression of LINC01087 predicted a better prognosis in luminal BCs, while TNBC tumors that harbored lower levels of LINC01087 were associated with reduced relapse-free survival. Furthermore, bioinformatics analyses were performed on TNBC and luminal BC samples and suggested that the putative tumor suppressor activity of LINC01087 may rely on interferences with pathways involved in cell survival, proliferation, adhesion, invasion, inflammation and drug sensitivity. Altogether, these data suggest that the assessment of LINC01087 deregulation could represent a novel, specific and promising biomarker not only for the diagnosis and prognosis of luminal BC subtypes and TNBCs, but also as a predictive biomarker of pharmacological interventions.